2006
DOI: 10.1152/ajprenal.00363.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protection against cisplatin-induced nephrotoxicity by a carbon monoxide-releasing molecule

Abstract: Nephrotoxicity is one of the main side effects caused by cisplatin (CP), a widely used antineoplastic agent. Here, we examined the effect of a novel water-soluble carbon monoxide-releasing molecule (CORM-3) on CP-mediated cytotoxicity in renal epithelial cells and explored the potential therapeutic benefits of carbon monoxide in CP-induced nephrotoxicity in vivo. Exposure of LLC-PK(1) cells to CP (50 microM) caused significant apoptosis as evidenced by caspase-3 activation and an increased number of floating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 33 publications
10
87
0
1
Order By: Relevance
“…37 In addition, CO releasing molecules have also been successfully tested for cytoprotection in cisplatin-mediated cell injury. 38 Therefore, we can not definitely rule out that effects other than HIF stabilization contribute to the in the protective effect of CO observed in our experiments.…”
Section: Discussionmentioning
confidence: 71%
“…37 In addition, CO releasing molecules have also been successfully tested for cytoprotection in cisplatin-mediated cell injury. 38 Therefore, we can not definitely rule out that effects other than HIF stabilization contribute to the in the protective effect of CO observed in our experiments.…”
Section: Discussionmentioning
confidence: 71%
“…HO-1 overexpression or CO administration has been shown to protect experimental kidney transplants from ischemia-reperfusion injury (4,30). Moreover, the administration of CO donor compounds, namely carbon monoxide-releasing molecules (CORM-3), protected against cisplatin nephrotoxicity and ischemia-reperfusion-induced renal injury (44,47). A recent report also demonstrated that hemin, a chemical inducer of HO-1, decreased renal injury and interstitial fibrosis in UUO (18).…”
Section: Discussionmentioning
confidence: 99%
“…A watersoluble, CO-releasing molecule (CORM-3) (Clark et al, 2003;Motterlini et al, 2005) was used as a source of exogenous CO to assess the contribution of this HO product on oxidant-mediated toxicity. In a control experiment, an inactive form of CORM-3 (iCORM-3) that is not capable of releasing CO was used as described before (Clark et al, 2003;Motterlini et al, 2005;Tayem et al, 2006). Cell viability was expressed as a percentage of the optical density in untreated cells from three experiments carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%